Exploring new media influences on social engagement among youths in Malaysia - Mohamed Nawi, Nul Widaya (2022)
The influence of new media on social engagement among Malaysian youths is increasingly challenging. In the past, the issues of youth social problems arose only in a relatively limited scope, but now issues, especially those that are at risk straightforward influence youth through new media. Some youths can process information, interpret, and provide feedback by showing positive behaviour. Among the factors trapped in youth in social engagement is the lack of an empirical information-based mindset by investigating first before believing something. This erroneous belief system forms values and attitudes that make them vulnerable to unhealthy and risky activities. Today's youth are urged to strengthen their internal and external assets and polish their potential to achieve excellent quality and well-being. This study related to the exploration that youth social problems are caused by the influence of new media where youth are exposed to information without borders. The study’s objective is to explore new media’s dependency on social engagement among youth. Apart from that is to explore how new media influence youth toward social engagement, explore the recent trends in further media usage, how the new media contributes to enhancing identity among Malaysian youth and study the behaviours of users towards new media use in daily life. This study will explore qualitative research using Focus Group Discussion (FGD), in-depth interviews and document analysis on the use of new media among youth. Two (2) theories have been discussed as guidelines studies: Media Dependency Theory and KAP Theory. Researchers conclude 14 Themes; 28 Categories, and 175 Codes based on the Themes and Categories and make the final statement by interpreting the research findings. Researchers analyse the data and find out the dependency of new media on social engagement among youth in Malaysia. The researcher divides the implication into two (2) significant perspectives: implication to theory and implication to the practice including Law Enforcement on Cyber Security Threats, Powers and Implementing Bodies in Controlling Cyber Security Malaysia and Cyber Law Implementation in Malaysia. The importance of study is paramount in terms of the needs of the government in formulating relevant new policies.